Cyclohexyl-diimine capped lower rim 1, 3-di-derivatized calix[4]arene conjugate as sensor for Al3+ by spectroscopy, microscopy, titration calorimetry and DFT computations. Issue 7 (3rd July 2018) - Nehra, Anita; Yarramala, Deepthi S.; Bandaru, Sateesh; Pulla Rao, Chebrolu
Abstract: A cyclohexane- trans -1, 2-diimine capped conjugate of 1, 3-calix[4]arene (L ) has been synthesized and characterized using different analytical and spectral techniques.L has been shown to be sensitive toward Al 3+ by exhibiting 45-fold enhancement in its emission intensity at 445 nm upon complexation. All the other 15 metal ions showed almost no or minimal change in the fluorescence intensity of theL supporting that none of those 15 ions is sensed byL . The complexation betweenL and Al 3+ has been further confirmed by absorption spectroscopy, isothermal titration calorimetry and ESI MS. The isotopic peak pattern of the ESI MS peak clearly confirmed the presence of aluminum in the 1:1 complex formed. The need for the flexible cap moiety for bringing selectivity to Al 3+ was proven by comparing the titration studies with the corresponding control molecules. The sensing of Al 3+ byL in the solid powder was demonstrated by fluorescence microscopy. The supramolecular behavior ofL changes from simple spherical type morphology inL to an aggregated micro pots and fibers upon Al 3+ binding. The DFT computational study yielded a distorted tetrahedral complex of the dianionic receptor resulting in AlN2 O2 core. Abstract :